Clinical characteristics and diagnostic imaging of cranial osteoblastoma. Issue 3 (March 2015) - Pelargos, Panayiotis E.; Nagasawa, Daniel T.; Ung, Nolan; Chung, Lawrance K.; Thill, Kimberly; Tenn, Stephen; Gopen, Quinton; Yang, Isaac
Abstract Benign osteoblastoma is a rare, vascular, osteoid-forming bone tumor that occurs even less frequently in the cranial bones. Benign osteoblastoma of the cranium affects women slightly more often than men and typically presents in the first three decades of life. Although clinical presentation can vary depending on location, cranial osteoblastoma usually presents as a painful, non-mobile, subcutaneous mass or swelling. On CT scan, it generally presents as a well-demarcated, mixed lytic and sclerotic lesion, with enlarged diploe, thinning outer and/or inner tables, and varying degrees of calcification. It is hypo to isointense on T1-weighted MRI and has variable presentation on T2-weighted MRI. Gross total resection is the definitive treatment, while subtotal resection is utilized when it is necessary to preserve critical adjacent neurovascular structures.